Capaian indikator kapitasi berbasis kinerja (KBK) dan faktor yang menghambat - Taufiqqurokhim, Taufiqqurokhim; Amirus, Khoidar; Sari, Nurhalina; Muhani, Nova (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Performance-Based Capitation Payments, hereinafter referred to as KBK Payments, are adjustments to the amount of capitation rates based on the results of an assessment of achievement of agreed individual health service indicators in the form of performance results of First Level Health Facilities in the context of improving service quality. The indicators referred to are the number of contacts, the ratio of non-specialist outpatient referrals and the ratio of controlled prolanis participants. Purpose: To determine Performance-Based Capitation Indicator Achievements (Kbk) and Inhibiting Factors Method: This study uses a qualitative case study approach using in-depth interviews, observation, and document review as a way to collect data. There were five informants in this study, namely the Head of the Health Center, General Practitioner, PIC JKN, PIC P-Care, PIC Prolanis. Data analysis in qualitative research consists of the stages of data reduction, data presentation, drawing conclusions, and verification. Results: The contact number indicator was not achieved because people were afraid to go to the puskesmas for treatment and health visit activities were not carried out during the COVID-19 pandemic so that sick visits and health visits decreased. Conclusion: The outpatient referral ratio for non-specialist cases was not achieved more due to the lack of understanding of the participants regarding the referral flow. Prolanis activities did not run optimally such as medical consultations, education of prolanis participant groups and monitoring of health status while home visits, SMS Gateway reminders and club activities did not done. Keywords: Indicators; Inhibiting Factors; Performance-Based Capitation (CBC). Abstrak Pendahuluan: Pembayaran Kapitasi Berbasis Kinerja, yang selanjutnya disebut dengan Pembayaran KBK, adalah penyesuaian besaran tarif kapitasi berdasarkan hasil penilaian pencapaian indikator pelayanan kesehatan perseorangan yang disepakati berupa hasil kinerja Fasilitas Kesehatan Tingkat Pertama dalam rangka peningkatan mutu pelayanan. Adapun indikator dimaksud adalah angka kontak, rasio rujukan rawat jalan non spesialistik dan rasio peserta prolanis terkendali. Tujuan: Untuk mengetahui Capaian Indikator Kapitasi Berbasis Kinerja (Kbk) Dan Faktor Yang Menghambat Metode: Penelitian ini menggunakan pendekatan kualitatif studi kasus dengan menggunakan metode wawancara mendalam, observasi, dan telaah dokumen sebagai cara untuk mengumpulkan data. Informan penelitian ini berjumlah lima orang, yaitu Kepala Puskesmas,Dokter umum, PIC JKN, PIC P-Care, PIC Prolanis. Analisis data dalam penelitian kualitatif terdiri dari tahap reduksi data, penyajian data, penarikan kesimpulan, dan verifikasie. Hasil: Tidak tercapainya indikator angka kontak disebabkan karena masyarakat takut berobat ke puskesmas dan tidak terlaksananya kegiatan kunjungan sehat pada masa pandemi COVID-19 sehingga kunjungan sakit dan kunjungan sehat menurun. Simpulan: Rasio rujukan rawat jalan kasus non spesialistik tidak tercapai lebih di sebabkan oleh belum pahamnya peserta terkait alur rujukan, Kegiatan prolanis tidak berjalan optimal seperti konsultasi medis, edukasi kelompok peserta prolanis dan pemantauan status kesehatan sedangkan home visit, reminder SMS Gateway dan aktivitas klub tidak terlaksana. Kata Kunci : Faktor Penghambat; Indikator; Kapitasi Berbasis Kinerja (KBK).